2020
DOI: 10.4236/jsea.2020.137010
|View full text |Cite
|
Sign up to set email alerts
|

Software Effort Prediction Using Ensemble Learning Methods

Abstract: Software Cost Estimation (SCE) is an essential requirement in producing software these days. Genuine accurate estimation requires cost-and-efforts factors in delivering software by utilizing algorithmic or Ensemble Learning Methods (ELMs). Effort is estimated in terms of individual months and length. Overestimation as well as underestimation of efforts can adversely affect software development. Hence, it is the responsibility of software development managers to estimate the cost using the best possible techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…With an MMRE value of 10% and a PRED(0.25) of 97%, the M5 rule ensemble was found to be the best way to estimate effort. 66 The above are some experimental studies on ensemble methods that are performed from time to time. Table 1 summarizes other related work on software effort estimation of various single methods using known datasets and real-time industrial projects, and the performance metrics were evaluated to determine the best model for estimating effort accuracy.…”
Section: Ensemble Effort Estimation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With an MMRE value of 10% and a PRED(0.25) of 97%, the M5 rule ensemble was found to be the best way to estimate effort. 66 The above are some experimental studies on ensemble methods that are performed from time to time. Table 1 summarizes other related work on software effort estimation of various single methods using known datasets and real-time industrial projects, and the performance metrics were evaluated to determine the best model for estimating effort accuracy.…”
Section: Ensemble Effort Estimation Methodsmentioning
confidence: 99%
“…The authors conducted a comparative study of 12 ensemble methods for effort estimation. With an MMRE value of 10% and a PRED(0.25) of 97%, the M5 rule ensemble was found to be the best way to estimate effort 66 …”
Section: Related Workmentioning
confidence: 99%
“…The results of this experiment showed that the effort accuracy equals 85% when applying a solo method and 91.35% using the combined classifiers. Alhazmi 41 examined the effect of two feature selection algorithms Best Fit and GA on six ensemble learning algorithms. The GA feature selection for the bagging M5Rule was the best method for predicting software effort.…”
Section: Related Workmentioning
confidence: 99%
“…and Khan, M.Z. [41] examined the effect of two feature selection algorithms Best Fit and Genetic Algorithm on six ensemble learning algorithms. The Genetic Algorithm (GA) feature selection for the bagging M5Rule was the best method for predicting software development effort.…”
Section: Figure 1 Categorization Of Effort Estimation Modelsmentioning
confidence: 99%
“…MMRE, PRED-prediction at 0.25, 0.50, and 0.75 power levels, Root Relative Squared Error, and Relative Absolute Error are used as evaluation measures. In this paper, a feature selection technique[18] based on CfsSubsetEval with BestFit and a genetic algorithm is applied. Based on the results, the best way to estimate software work is through genetic algorithm feature selection for M5Rule.Halcyon and colleagues offered eight different ensemble approaches for estimating effort.…”
mentioning
confidence: 99%